'They wrote "gay" on her file': transgender Ugandans in HIV prevention and treatment. Issue 1 (2nd January 2016) - Minor Peters, Melissa
Abstract: This paper examines the ways in which HIV-related programmes for heterosexual Ugandans and also for men who have sex with men work to deny healthcare services to transgender people in Uganda. Contrary to current conventional wisdom, the study found that the widespread use of the term 'men who have sex with men' produces greater barriers to healthcare for queer Ugandans than identity categories such as 'lesbian' or 'transgender'. Interventions for men who have sex with men assume a male-identified sexual subject with agency over sexual practices, such as frequency of condom use. Based on two years of ethnographic research in Kampala, I suggest that the focus on individual sexual practices harms transgender people in two ways. First, current HIV prevention and treatment programmes fail to account for risk factors that accrue to both male and female transgender Ugandans due to the social enforcement of gender norms. Second, the term men who have sex with men directs attention towards stigmatised sexual practices, producing the neglect and abuse of non-heteronormative individuals. In the context of Ugandan healthcare, terms such as 'transgender' and kuchu instead focus attention on the dignity and humanity of the rights-bearing person. These findings emphasise how health practitioners must pay attention to emic categories in order to address the ways in which vulnerability is distributed along social vectors of difference.